3i+3=2i+9

Simple and best practice solution for 3i+3=2i+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3i+3=2i+9 equation:



3i+3=2i+9
We move all terms to the left:
3i+3-(2i+9)=0
We get rid of parentheses
3i-2i-9+3=0
We add all the numbers together, and all the variables
i-6=0
We move all terms containing i to the left, all other terms to the right
i=6

See similar equations:

| (6^x)/36=216 | | (D^(4)+3D^(3)-6D^(2)-28D-24)y=0 | | 4(8-2e)=64 | | 3a-7=140 | | (D^4+3D^3-6D^2+28D-24)y=0 | | 2^t=200 | | -74=9(d-2)-11 | | 40/(n+5)=5/2 | | 66x-5/4=0 | | 27=-3(y-3) | | k=43 | | 5(×+4)=3(x+10) | | 40/(n-5)=5/2 | | b−10.7=13.3 | | x=18x-1 | | 3.9=1.80x | | x+6.6=11.6 | | 5z+15=75-25z | | -0.67(15x+3)=-3x-9 | | 10.x=20/24 | | 3x-4=6x+9 | | x+.75x=1308.69 | | n/3×n=2×9 | | 16x-8=8+14x | | 5×2x=5/16 | | 2(3v-5)=2(v-11 | | 11=-b/3+10 | | 120+x=115° | | 2y+9=27-4 | | 15-6w=9 | | 3(3c-2)=5(-2c-1) | | 2=-10r+8r |

Equations solver categories